PNNS-Conjugated Chitosan Mediated IGF-1 and miR-140 Overexpression in Articular Chondrocytes Improves Cartilage Repair. (21st March 2019) - Zhao, Rong-lan; Zhang, Xu-mei; Jia, Li-na; Song, Wei; Sun, Yan-li; Meng, Xiang-ying; Peng, Xiao-xiang
Abstract : The aim of the present study was to investigate the effects of phosphorylatable nucleus localization signal linked nucleic kinase substrate short peptide (N N S p )-conjugated chitosan (N N S p -CS) mediated miR-140 and IGF-1 in both rabbit chondrocytes and cartilage defects model.N N S p -CS was combined with pBudCE4.1-IGF-1, pBudCE4.1-miR-140, and negative control pBudCE4.1 to form pDNA/N N S p -CS complexes. Then these complexes were transfected into chondrocytes or injected intra-articularly into the knee joints. High levels of IGF-1 and miR-140 expression were detected both in vitro and in vivo . Compared with pBudCE4.1 group, in vitro, the transgenic groups significantly promoted chondrocyte proliferation, increased glycosaminoglycan (GAG) synthesis, and ACAN, COL2A1, and TIMP-1 levels, and reduced the levels of nitric oxide (NO), MMP-13, and ADAMTS-5. In vivo, the exogenous genes enhanced COL2A1, ACAN, and TIMP-1 expression in cartilage and reduced cartilage Mankin score and the contents of NO, IL-1 β, TNF- α, and GAG contents in synovial fluid of rabbits, MMP-13, ADAMTS-5, COL1A2, and COL10A1 levels in cartilage. Double gene combination showed better results than single gene. This study indicate thatN N S p -CS is a better gene delivery vehicle in gene therapy for cartilage defects and that miR-140 combination IGF-1 transfection has better biologic effects on cartilage defects.